Implementing public health vending machines on the reservation lands of the Bois Forte Band of Chippewa (United States) - Sean T. Allen; Kristin E. Schneider; Maisie Conrad; Pam Hughes; Allison O’Rourke; Molly C. Reid; Cathy Chavers; Christopher G. Kemp; Melissa Walls (Harm Reduction Journal)
Abstract Background Public health vending machines (PHVMs) have been shown to improve access to numerous health-promoting supplies. However, they are understudied in the United States and no study of which we are aware has examined their implementation on American Indian reservation lands. Objective This study describes how PHVMs were implemented on the Bois Forte Band of Chippewa Reservation lands in Minnesota (United States) and associated costs during the first 24 weeks of operations. Methods We summarize the steps undertaken to implement PHVMs on reservation lands. We describe formative research in which we assessed willingness to use a PHVM among a sample of people who use drugs. Then, we describe how we worked with community members to ensure the appropriateness of a PHVM initiative. Finally, we present utilization data from the first 24 weeks of PHVM operations and describe associated implementation costs. Results In May 2022, the academic research team presented to the Bois Forte Reservation Tribal Council about PHVMs and requested a Resolution that authorized their implementation on Reservation lands. The Resolution was unanimously approved, and the team began working with a local Community Research Council to determine the most appropriate way to implement the PHVMs. Prior to implementation, we conducted a survey among people who used drugs (N = 227) on Reservation lands and found that most (56%) reported willingness to use PHVMs if they were available. In October 2023, two PHVMs were installed. During the first 24 weeks of operations, there were 2,534 successful dispensations at the PHVMs. Items dispensed through the PHVMs included COVID-19 test kits, naloxone, drug test strip kits, menstrual supply kits, wound care kits, sterile injection equipment kits, pregnancy tests, safer sex kits, and HIV self-test kits. In total, the PHVM initiative cost approximately $30,406.75 (USD) during its initial 24-week implementation period. Conclusions The Bois Forte Band of Chippewa took swift action upon learning about the potential public health benefits of PHVMs and immediately authorized their implementation, catalyzing a collaborative effort between local community members and academic partners. Thousands of life-sustaining supplies were dispensed at the PHVMs, supporting the prevention and treatment needs of the community.